Integrity test (core drilling method, sound wave transmission method, and etc.) of constructed diaphragm wall for Brac University at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Zhejiang Zhongcheng Detection Technology Co. Ltd. for integrity test (core drilling method, sound wave transmission method, and etc.) of constructed diaphragm wall for Brac University new campus project.